Al-Makar ‘Inda Wahbah al-Zuhaily Fî al-Tafsîr al-Munîr - Ilham Habibullah; Abdullah Azzam (Universitas Darussalam Gontor, 2019)
Treason is one of the big issues today that has been much discussed and especially in the national politics. Some people think that treason is only a coup attempt against a legitmate government, and even more alarming is the alleged treason against Muslims which is very contrary to the facts. One example is an action of 212 in Monas Jakarta in 2016, where some people are accused of treason against the government. From those information then the author intends to discuss and examine the concept of treason according to Wahbah Zuhaili revelation in tafsir Al-Munir. From this discussion the researcher concludes that Zuhaili interpret the meaning of treason in letter Fathir verse 10 which means bad deeds done by deceit and trickery such as imprisoning, murder expulsion, pretend obedient to God when he hate and effort for weaking muslims. And in letter Al-An’am verse 124 it means a deeds done clandestinely and gently in the arrogant deceptions and tricks of following in the footsteps of the prophet and the straight path he carries. And in letter Al-Anfal verse 30 it means trickery to inflict something hated unnoticed such as imprisoning, killing, and expelling from the homeland.